Quantifying the offensive sequences that result in goals in elite futsal matches - Sarmento, Hugo (2016)
The aim of this study was to quantify the type of offensive sequences that result in goals in elite futsal. Thirty competitive games in the Spanish Primera Division de Sala were analysed using computerised notation analysis for patterns of play that resulted in goals. More goals were scored in positional attack (42%) and from set pieces (27%) compared to other activities. The number of defence to offense "transitions" (n = 45) and the start of offensive plays due to the rules of the game (n = 45) were the most common type of sequences that resulted in goals compared to other patterns of play. The central offensive zonal areas were the most common for shots on goal, with 73% of all goals scored from these areas of the pitch compared to defensive and wide zones. The foot was the main part of the body involved in scoring (n = 114). T-pattern analysis of offensive sequences revealed regular patterns of play, which are common in goal scoring opportunities in futsal and are typical movement patterns in this sport. The data demonstrate common offensive sequences and movement patterns related to goals in elite futsal and this could provide important information for the development of physical and technical training drills that replicate important game situations.